Field relationships and petrology of the Late Devonian Fisset Brook Formation in the Cheticamp area, western Cape Breton Island, Nova Scotia - Barr, Sandra M.; Peterson, Kevin C.A. (Atlantic Geology, 1998)
The Fisset Brook Formation in the Cheticamp area forms two elongate belts, a western belt which includes the type section of the formation in Fisset Brook and a separate eastern belt. In the western belt, the Fisset Brook Formation consists of (1) a lower, mainly sedimentary unit dominated by a basal conglomerate that overlies Proterozoic to Silurian metamorphic and igneous rocks, (2) a dominant middle part that consists of basaltic flows interlayered with minor red clastic sedimentary rocks, and (3) an upper part that consists mainly of rhyolite flows and tuffs. In the eastern belt, the basal sedimentary unit appears to be absent due to faulting, and the upper felsic unit is thicker than in the western belt. Mafic dykes in overlying sedimentary strata of the Creignish Formation (Horton Group) are petrochemically similar to basalt in the Fisset Brook Formation, and may represent the waning stages of igneous activity in the area, or a separate minor Late Devonian to Early Carboniferous igneous event. Petrological studies of an extensive suite of samples support the results of earlier studies showing that the mafic volcanic rocks are continental, within-plate tholeiites. The rhyolites are similar to within-plate felsic rocks, but lack elevated values of elements such as Zr and Nb that characterize A-type granites. They are probably the extrusive equivalents of voluminous granites of similar age in the Cape Breton Highlands, suggesting that the present exposures of the Fisset Brook Formation may be remnants of more extensive sequences. The stratigraphy, lithology, age, and petrochemical characteristics of the Fisset Brook Formation in the Cheticamp area are very similar to those in the Gillanders Mountain-Lake Ainslie area. RÉSUMÉ La Formation de Fisset Brook dans la region de Chéticamp forme deux ceintures allongees, une ceinture occidentale renfermant le stratotype de la Formation dans le secteur du ruisseau Fisset et une ceinture orientale séparée. Dans la ceinture ...